Segment 2 from influenza A(H1N1) 2009 pandemic viruses confers temperature-sensitive haemagglutinin yield on candidate vaccine virus growth in eggs that can be epistatically complemented by PB2 701D. (6th June 2019) - Hussain, Saira; Turnbull, Matthew L.; Pinto, Rute M.; McCauley, John W.; Engelhardt, Othmar G.; Digard, Paul
Abstract : Candidate vaccine viruses (CVVs) for seasonal influenza A virus are made by reassortment of the antigenic virus with an egg-adapted strain, typically A/Puerto Rico/8/34 (PR8). Many 2009 A(H1N1) pandemic (pdm09) high-growth reassortants (HGRs) selected this way contain pdm09 segment 2 in addition to the antigenic genes. To investigate this, we made CVV mimics by reverse genetics (RG) that were either 6 : 2 or 5 : 3 reassortants between PR8 and two pdm09 strains, A/California/7/2009 (Cal7) and A/England/195/2009, differing in the source of segment 2. The 5 : 3 viruses replicated better in MDCK-SIAT1 cells than the 6 : 2 viruses, but the 6 : 2 CVVs gave higher haemagglutinin (HA) antigen yields from eggs. This unexpected phenomenon reflected temperature sensitivity conferred by pdm09 segment 2, as the egg HA yields of the 5 : 3 viruses improved substantially when viruses were grown at 35 °C compared with 37.5 °C, whereas the 6 : 2 virus yields did not. However, the authentic 5 : 3 pdm09 HGRs, X-179A and X-181, were not markedly temperature sensitive despite their PB1 sequences being identical to that of Cal7, suggesting compensatory mutations elsewhere in the genome. Sequence comparisons of the PR8-derived backbone genes identified polymorphisms in PB2, NP, NS1 and NS2. Of these, PB2 N701D affected the temperature dependence of viral transcription and, furthermore, improved and drastically reduced the temperature sensitivity of the HA yield from the 5 : 3 CVV mimic. We conclude that the HA yield of pdm09 CVVs can be affected by an epistatic interaction between PR8 PB2 and pdm09 PB1, but that this can be minimized by ensuring that the backbones used for vaccine manufacture in eggs contain PB2 701D.